Successful management of malignant colovesical fistula using covered colonic self-expanding metallic stent: a case report - Goro Takahashi; Akihisa Matsuda; Takeshi Yamada; Kay Uehara; Seiichi Shinji; Yasuyuki Yokoyama; Takuma Iwai; Kohki Takeda; Sho Kuriyama; Toshimitsu Miyasaka; Shintaro Kanaka; Tai Terayachi; et al. (Surgical Case Reports, 2023)
Abstract Background A colovesical fistula (CVF) is commonly treated by resection of the intestine containing the fistula or creation of a defunctioning stoma. We herein report a case of successful fistula closure and avoidance of colostomy after placement of a covered colonic self-expanding metallic stent (SEMS) as a palliative treatment for a malignant CVF. Case presentation A 75-year-old man undergoing infusional 5-fluorouracil and irinotecan chemotherapy plus bevacizumab for recurrent peritoneal dissemination of rectal cancer was admitted to our hospital because of fecaluria with a high-grade fever. Blood tests showed a moderate inflammatory reaction (white blood cell count, 9200/mm3; C-reactive protein, 11.03 mg/dL; procalcitonin, 1.33 ng/mL). Urinary sediment examination showed severe bacteriuria. Abdominal contrast-enhanced computed tomography showed intravesical gas, thickening of the posterior wall of the bladder, and irregular thickening of the sigmoid colon wall contiguous with the posterior bladder wall. Magnetic resonance imaging (MRI) clearly showed a fistula between the bladder and sigmoid colon. Colonoscopy revealed a circumferential malignant stricture 15 cm from the anal verge, and a fistula to the bladder was identified by water-soluble contrast medium. We diagnosed a complicated urinary tract infection (UTI) associated with a CVF due to peritoneal dissemination and started empirical treatment with sulbactam/ampicillin. Given the absence of active inflammatory findings around the fistula on MRI and the patient’s physical frailty, we decided to place a covered SEMS to close the fistula. Under fluoroscopic and endoscopic guidance, a covered colonic SEMS of 80-mm length and 20-mm diameter was successfully deployed, and the fistula was sealed immediately after placement. Urine culture on day 3 after stenting was negative for bacteria, and a contrast study on day 5 showed no fistula. The patient was discharged home on day 6 with no complications. The UTI did not recur for 4 months after discharge. Conclusions A covered colonic SEMS was useful for sealing a malignant CVF in a patient unfit for surgery, and MRI was valuable to determine the status of the fistula. A covered colonic SEMS could be an alternative to surgical treatment for CVFs in patients who require palliative care.